Sub-10 nm mixing and alloying of Cu-Ag and Cu-Ni via accelerated solid diffusion - Dai, Haiwen (2023)
Development of nanoscale multicomponent solid inorganic materials is often hindered by slow solid diffusion kinetics and poor precursor mixing in conventional solid-state synthesis. These shortcomings can be alleviated by combining nanosized precursor mixtures and low temperature reaction, which could reduce crystal growth and accelerate the solid diffusion at the same time. However, high throughput production of nanoparticle mixtures with tunable composition via conventional synthesis is very challenging. In this work, we demonstrate that ∼10 nm homogeneous mixing of sub-10 nm nanoparticles can be achieved via spark nanomixing at room temperature and pressure. Kinetically driven Spark Plasma Discharge nanoparticle generation and ambient processing conditions limit particle coarsening and agglomeration, resulting in sub-10 nm primary particles of as-deposited films. The intimate mixing of these nanosized precursor particles enables intraparticle diffusion and formation of Cu/Ni nanoalloy during subsequent low temperature annealing at 100 °C. We also discovered that cross-particle diffusion is promoted during the low-temperature sulfurization of Cu/Ag which tends to phase-segregate, eventually leading to the growth of sulfide nanocrystals and improved homogeneity. High elemental homogeneity, small diffusion path lengths, and high diffusibility synergically contribute to faster diffusion kinetics of sub-10 nm nanoparticle mixtures. The combination of ∼10 nm homogeneous precursors via spark nanomixing, low-temperature annealing, and a wide range of potentially compatible materials makes our approach a good candidate as a general platform toward accelerated solid state synthesis of nanomaterials.